2011
DOI: 10.2478/v10181-011-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Local immunity of the respiratory mucosal system in chickens and turkeys

Abstract: This review article presents fundamental mechanisms of the local mucosal immunity in selected regions of the respiratory tract in healthy birds and in some pathological conditions. The respiratory system, whose mucosa come into direct contact with microorganisms contaminating inhaled air, has some associated structures, such as Harderian gland (HG), conjunctive-associated lymphoid tissue (CALT) and paranasal glands (PG), whose participation in local mechanisms of the mucosal immunity has been corroborated by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Local immunity of the respiratory mucosal system is ensured by nonspecific defensive reactions with an arsenal of mechanical and cellular defenses, supplemented when necessary by inflammatory and immune responses. [75][76][77] There is no constitutive lymphoid tissue in the trachea. However, studies investigating infections of the respiratory system have shown reactivity of the tracheal mucosa to infections, despite a lack of essential lymphoid tissue.…”
Section: Upper Respiratory Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…Local immunity of the respiratory mucosal system is ensured by nonspecific defensive reactions with an arsenal of mechanical and cellular defenses, supplemented when necessary by inflammatory and immune responses. [75][76][77] There is no constitutive lymphoid tissue in the trachea. However, studies investigating infections of the respiratory system have shown reactivity of the tracheal mucosa to infections, despite a lack of essential lymphoid tissue.…”
Section: Upper Respiratory Tractmentioning
confidence: 99%
“…Conjunctivalassociated lymphoid tissue and nasal-associated lymphoid tissue, which are at the forefront of defense, are not fully functional germinal center and plasmatic cells at 4 weeks of age. 76,79 Further, B-cell responses were not detected in the trachea until 3 weeks post-infection in layer-type chickens, which is typically more than half the lifespan of the average broiler. Having assessed the high risk of contamination of chickens through the aerosol route in hatcheries, these structures appear to have a minute role in preventing infections acquired through inhalation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Harderian gland (HG) located behind the orbit of the eye plays a role in adaptive immune response, producing numerous immunoglobins and probably presenting antigens (del Cacho et al 1992, Śmiałek et al 2011, Gurjar et al 2013. Since the intraocular route is widely used in vaccination of chicken with live-attenuated viruses and bacteria (Purswell et al 2010, Gurjar et al 2013, it is important to know if this way of administration of class B CpG ODN can elicit the proinflamatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Humoral immunity of the body mucous membranes is associated with IgA (also reffered to as secretory IgA -sIgA) (Snoeck et al 2006, Smialek et al 2011.…”
mentioning
confidence: 99%